2019
DOI: 10.1111/avj.12845
|View full text |Cite
|
Sign up to set email alerts
|

DVM students report higher psychological distress than the Australian public, medical students, junior medical officers and practicing veterinarians

Abstract: Aim To measure the stress levels of Doctor of Veterinary Medicine (DVM) students at the University of Sydney using the Kessler Psychological Distress Scale (K10) questionnaire.Methods DVM students in years 1 to 4 were surveyed in semester 2 of 2018. The voluntary online survey consisted of 6 demographic questions and the K10 scale, a standardised measure of stress commonly used in Australia by medical practitioners for evaluation and referral to mental health professionals. Academic year cohorts were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…Based on normative samples for the DASS‐D, a “moderate” or higher score indicates that a student is experiencing more depressive symptoms than 81% of the population 53 . The finding that depression scores in veterinary students were not higher than students from other academic disciplines is in contrast to previous studies that have found veterinary students experience higher levels of psychological distress compared to other student groups (e.g., medical students 14 ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Based on normative samples for the DASS‐D, a “moderate” or higher score indicates that a student is experiencing more depressive symptoms than 81% of the population 53 . The finding that depression scores in veterinary students were not higher than students from other academic disciplines is in contrast to previous studies that have found veterinary students experience higher levels of psychological distress compared to other student groups (e.g., medical students 14 ).…”
Section: Discussionmentioning
confidence: 69%
“…Of concern, a recent study of 573 veterinary students in the United States found 24% of students had engaged in self‐harm (e.g., burning or cutting behaviours) and 30% reported having seriously thought about suicide at some point in their studies 12 . Australian research findings indicate veterinary students in Australia display levels of severe stress, approximately 2.42 times higher than engineering students, 13 and significantly higher levels of psychological distress than medical students and the Australian general population 14 . Despite the reported levels of stress and depression among veterinary students, minimal research has been conducted to understand predictive factors of depression in this population, and in particular, within the Australian context.…”
Section: Stress In Veterinary Studentsmentioning
confidence: 98%
“…Recent studies have indicated that 34% of veterinary students in North America experience clinical levels of depression, and just over half of those students reported that their symptoms made it very to extremely difficult to perform routine tasks such as taking care of things at home (Karaffa & Hancock, 2019). Other research revealed similar findings with student populations in Australia (Yang, Ward, & Fawcett, 2019). Yang et al (2019) reported 53.2% of veterinary student respondents having high or very high scores on a measure of psychological distress, notably much higher than medical students (22.1%), practicing veterinarians (14%), or the general population (11.7%).…”
Section: Introductionmentioning
confidence: 85%
“…Yang et al (2019) reported 53.2% of veterinary student respondents having high or very high scores on a measure of psychological distress, notably much higher than medical students (22.1%), practicing veterinarians (14%), or the general population (11.7%). Both Yang, Ward, and Fawcett (2019) and Karaffa and Hancock (2019) reported that women have significantly higher levels of distress.…”
Section: Introductionmentioning
confidence: 99%
“…As signi cant correlations exist between stress, anxiety, and depression (Rawson et al 1994), such interrelationships suggest that veterinary students increasingly experience signi cantly higher level of such stressors. Veterinary students experience higher levels of psychological stress as compared to medical students (Yang et al 2019). Certain other reports have claimed that the veterinary student population, experiences stress as a result of information overload, with an emphasis on the need for rote learning, and that students can be at risk of burn-out as they have been loaded with the range of demands on them (Bushby, 1994).…”
Section: Introductionmentioning
confidence: 99%